Metapetrocosmea alba (Gesneriaceae), a new species from central Vietnam - Zheng, Xi-Rong; Zou, Pei-Shan; Chen, Ying; Vu, Tien-Chinh; Dai, Se-Ping (Phytotaxa, 2023)
Based on morphological comparison and literature consultation, a new species, Metapetrocosmea alba (Gesneriaceae), is confirmed from Bach Ma National Park, central Vietnam. This new species is similar to M. poilanei, but differs by its longer and white funnelform corolla and three staminodes. And it is easy to distinguish the new species from M. cycnostyla by its distinct stem, and the shape and size of leaf blade. A detailed morphological description and photographic illustration of the new species are provided along with ecological information and geographic distribution.